Gold Reserves in Majority Non-Muslim Countries and Muslim Majority Countries - Cliff Kohardinata; Clarissa Rachmadella Roshidawati; Helena Sidharta (Universitas Gorontalo, 2021)
This study aims to analyse the priority of gold reserves compared to other reserves between non-Muslim countries with Muslim-majority countries, considering that Muslim scholars often put forward studies on gold or gold reserves, and even become a discourse on using gold as a transactional tool. The research methodology used in this study is a quantitative approach using secondary data. The results of this study indicated that non-Muslim majority countries more considering to use gold based on a reserve motive or precautionary motive for preventing risk. On the other hand, the precautionary motive has no effect on the decision of Muslim majority countries to prioritize gold as a reserve over other reserves.